Pengaruh Pendapatan Asli Daerah (PAD) Dan Dana Perimbangan Terhadap Kinerja Keuangan Pemerintah Kabupaten/Kota Di Provinsi Jawa Tengah - Wahyuningsih, Yoshinta Endah (2016)
The purpose of this study to examine the original income (PAD) effect on the financial performance of the government. to test the effect on the Balance Fund of the government's financial performance. The population in this study are 35 districts / cities in Central Java province that already has the data of the Regional Budget (APBD) in the period 2011-2013. This research uses descriptive statistical analysis, the classical assumption in the form of normality test, multicollinearity, autocorrelation test, heteroscedasticity test and test hypotheses in the form of test multiple linear regression analysis, statistical tests T, F statistical test, test the coefficient of determination (R2). The results of this study indicate that local revenues had no effect on the financial performance, while the fund balance adversely affect the financial performance as evidenced by the significant value of <0.05.